Português (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article aims to research the historical evolution of domestic work from colonization to the present day. It addresses their social, legal and remuneration advances, demonstrating the difficulty of recognizing the profession and labor rights. It also addresses the issue of slave domestic work and conditions analogous to slavery in which domestic workers are subjected to the present day. Finally, it addresses the Brazilian legislation that aims to combat slave labor in the country. For this purpose, the deductive and qualitative method will be adopted, through doctrinal research, scientific articles and legislation, aiming to bring to light reflections on the subject, with the motto of slave domestic work.